Trade Liberalization, Intermediate Inputs, and Productivity : Evidence from Indonesia - Amiti, Mary (IMF Working Papers; Working Paper ;, 2005)
This paper estimates the effects of trade liberalization on plant productivity. In contrast to previous studies, we distinguish between productivity gains arising from lower tariffs on final goods relative to lower tariffs on intermediate inputs. Lower output tariffs can produce productivity gains by inducing tougher import competition whereas cheaper imported inputs can raise productivity via learning, variety, or quality effects. We use Indonesian manufacturing census data from 1991 to 2001, which includes plant-level information on imported inputs. The results show that the largest gains arise from reducing input tariffs. A 10 percentage point fall in output tariffs increases productivity by about 1 percent, whereas an equivalent fall in input tariffs leads to a 3 percent productivity gain for all firms and an 11 percent productivity gain for importing firms.